2007
DOI: 10.1016/j.bmc.2007.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Activity of 7-methyljuglone derivatives against Mycobacterium tuberculosis and as subversive substrates for mycothiol disulfide reductase

Abstract: The naphthoquinone 7-methyljuglone (5-hydroxy-7-methyl-1,4-naphthoquinone) has previously been isolated and identified as an active component of root extracts of Euclea natalensis which displays antitubercular activity. Herein, a series of synthetic and plantderived naphthoquinone derivates of the 7-methyljuglone scaffold have been prepared and evaluated for antibacterial activity against Mycobacterium tuberculosis. Several of these compounds have been shown to operate as subversive substrates with mycothiol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 39 publications
3
89
1
Order By: Relevance
“…These compounds have also been isolated and identified in the shoots and also in the shoot extract used in this study (Bapela et al, 2007;Tannock, 1973;van der Vijver and Gerritsma, 1974). The compounds were selected based on their antimycobacterial activity (Mahapatra et al, 2007; van der Kooy et al, 2006). Molecular docking was performed using GOLD (Genetic Optimization for Ligand Docking) program (Jones et al, 1997).…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds have also been isolated and identified in the shoots and also in the shoot extract used in this study (Bapela et al, 2007;Tannock, 1973;van der Vijver and Gerritsma, 1974). The compounds were selected based on their antimycobacterial activity (Mahapatra et al, 2007; van der Kooy et al, 2006). Molecular docking was performed using GOLD (Genetic Optimization for Ligand Docking) program (Jones et al, 1997).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…According to previous research done, some plants have shown significant activity against Mycobacterium in in vitro studies, with a minimum inhibitory concentration (MIC) of lower than 50ug/ml. These plants include; Berchemia discolor with an MIC of 12.5 µg/ml, Warbugia salutaris (25 µg/ml), Terminalia sericea (25 µg/ml), Bridelia micrantha, and Diospyros mespiliformis (12.5 µg/ml) (Green et al, 2010;Mahapatra et al, 2007). Euclea natalensis, a plant belonging to the Ebenaceae family has been used by multiple communities in southern Africa including, Tsonga, Shangaan, Venda and the Zulu tribes.…”
Section: Introductionmentioning
confidence: 99%
“…1,4-Naphthoquinone is an important example of quinone family and is used as a raw material in pharmaceutical industries. 1,4-Naphthoquinone and its derivatives exhibited several interesting and different biological responses including antibacterial, 3 antifungal, 4,5 anti-inflammatory, antiplatelet, antiallergic, 6 antithrombotic, 7 antiviral, 8 anticancer, [9][10][11] apoptosis, 12 lipoxygenase, 13,14 radical scavenging 15 and anti-ringworm 16 activities. Recently, 1,4-Naphthoquinone derivatives were proved to be human DNA topoisomerase I and II inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…is used traditionally for the treatment of cancer in South Africa. 28,29 The metabolite 7-methyljuglone (7-MJ) previously isolated from this plant 3 , exhibited anticancer activity. A series of derivatives of 7-MJ were synthesized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation